Hubungan Kepemilikan Jamban dengan Kejadian Diare di Desa Bagan Laguh, Kecamatan Bunut, Riau: The Correlation Between Toilet Ownership With the Event of Diarrhea in Bagan Laguh Village, Bunut Sub-District, Riau - Nur Rizki Aprilia Utami; Tantri Analisawati Sudarsono; Retno Sulistiyowati; Supriyadi Supriyadi (Jurnal Surya Medika (JSM), 2023)
Diarrhea is an endemic disease that can cause Extraordinary Events (KLB). In 2017, there were 21 occurrences of diarrhea spreading across 12 provinces with a total of 1,725 patients and 34 deaths (CFR 1.97%). There are three risk factors for diarrhea, namely individual characteristics, preventive behavior, and environment. This research is to determine the correlation between toilet ownership and the occurrence of diarrhea in Bagan Laguh Village, Riau. The research population was all residents of Bagan Laguh Village listedin the Integrated Social Welfare Data (DTKS) and 59 residents were selected as the research sample using the simple random sampling technique. The primary data were obtained from the questionnaires filled out by the respondents and then analyzed using the Chi-Square test. The results of this research indicated that respondents' level of education and income are not significantly correlated with the occurrence of diarrhea(P values= 0.115 and 0.421 respectively); however, respondents' knowledge, attitude, and toilet ownership are correlated with the occurrence of diarrhea significantly (P-values = 0.007, 0.001, and 0.002 respectively).